ISLAMIC MAGAZINE ARTICLES TO ENHANCE STUDENTS’ READING SKILL AND BUILD THEIR CHARACTER VALUES - Munir, Munir; Hartono, Rudi (UPI Press, 2016)
This present study examined the use of Islamic magazine articles as authentic materials in teaching reading comprehension for the students of English Education Department of IAIN Batusangkar, Indonesia. This idea is based on the belief that students can be motivated and challenged to read if the selected materials pertain to their prior knowledge and experiences.Â In addition to this, using Islamic magazine articles as essential sources of information can positively expose students to real language. This study used qualitative research. This research was conducted to the third semester students. Observation and interview were used to collect data from 58 students who learned reading comprehension in the classroom. The research findings showed that the use of Islamic magazine articles empirically enhanced the studentsâ€™ reading performance and built their character values. Based on these findings it is recommended that lecturers of reading comprehension subject should be able to exploit up-to-date articles to be used as lesson materials in teaching reading comprehension at the English education department in order to avoid boredom in reading texts.